A Comparison of Er:YAG Laser with Photon-Initiated Photoacoustic Streaming, Nd:YAG Laser, and Conventional Irrigation on the Eradication of Root Dentinal Tubule Infection by Enterococcus faecalis Biofilms: A Scanning Electron Microscopy Study. (27th November 2017) - Ozses Ozkaya, Burcu; Gulsahi, Kamran; Ungor, Mete; Gocmen, Julide Sedef
Abstract : This study evaluated the antimicrobial efficacy of Er:YAG laser activation with photon-initiated photoacoustic streaming (PIPS), Nd:YAG laser disinfection, and conventional irrigation on Enterococcus faecalis biofilms using scanning electron microscopy (SEM). Biofilms were grown on 110 root halves and divided into the following: Groups 1 and 2 (saline and 1% NaOCl with apical position of PIPS, resp.), Groups 3 and 4 (saline and 1% NaOCl with coronal position of PIPS, resp.), Groups 5 and 6 (Nd:YAG laser after saline and 1% NaOCl irrigation, resp.) and Groups 7, 8, and 9 (conventional irrigation with 1% NaOCl, 6% NaOCl, and saline, resp.). SEM images of the apical, middle, and coronal levels were examined using a scoring system. Score differences between Groups 1 and 2 were insignificant at all levels in the remaining biofilm. Group 4 had significantly greater bacterial elimination than Group 3 at all levels. Differences in Nd:YAG laser irradiation between Groups 5 and 6 were insignificant. Groups 7 and 8 were insignificantly different, except at the middle level. Saline group had a higher percentage of biofilms than the others. In this study, PIPS activation with NaOCl eliminates more E. faecalis biofilms in all root canals regardless of the position of the fiber tip.